Mechanism of cysteine oxidation by peroxynitrite: an integrated experimental and theoretical study - Zeida Camacho, Ari Fernando (2013)
Since peroxynitrite was identified as a pathophysiological agent it has been implicated in a great variety of cellular processes. Particularly, peroxynitrite mediated oxidation of cellular thiol-containing compounds such as Cys residues, is a key event which has been extensively studied. Although great advances have been accomplished, the reaction is not completely understood at the atomic level. Aiming to shed light on this subject, we present an integrated kinetic and theoretical study of the oxidation of free Cys by peroxynitrite. We determined pH-independent thermodynamic activation parameters, namely those corresponding to the reaction between the reactive species: Cys thiolate and peroxynitrous acid. We found a pH-independent activation energy of 8.2 ± 0.6 kcal/mol. Simulations were performed using state of the art hybrid quantum-classical (QM-MM) molecular dynamics simulations. Our results are consistent with a SN2 mechanism, with Cys sulfenic acid and nitrite anion as products. The activation barrier is mostly due to the alignment of sulfur's thiolate atom with the oxygen atoms of the peroxide, along with the concomitant charge reorganization and important changes in the solvation profile. This work provides an atomic detailed description of the reaction mechanism and a framework to understand the environment effects on peroxynitrite reactivity with protein thiols.